Short Communication: Morphometric variations in two populations of Limnophora marginata Stein, 1904 (Diptera, Muscidae) in Ecuador - MARÍA ALEJANDRA RUIZ; CAMILA ACOSTA-LÓPEZ; ANA SOTO-VIVAS (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ruiz MA, Acosta-López C, Soto-Vivas A. 2021. Short Communication: Morphometric variations in two populations of Limnophora marginata Stein, 1904 (Diptera, Muscidae) in Ecuador. Biodiversitas 22: 2654-2657. Limnophora includes 230 species, eleven of which are present in Ecuador. There are few studies on the bioecology of these species in the country. However, recent studies indicate that Limnophora marginata Stein, 1904 as the most abundant species in the Evergreen High Montane Forest (EHMF) located at 3400 masl in Tocachi parish, in contrast to a low abundance in the Dry Forest (DF) at 2500 masl in Malchingui parish, Pedro Moncayo Canton. This study was described the wing morphogeometric variation of L. marginata associated with these two habitats. Thirty-two wings were photographed: 16 specimens in EHMF and 16 in DF. The coordinates configurations (x,y) were registered and aligned through Generalized Procrustes Analysis. The centroid size between habitats was significantly different (Kruskal-Wallis; p?0.005); EHMF specimens were larger than DF. Reclassification a posteriori was perfect in DF specimens (100%), and almost perfect in EHMF (93.75%). The landmarks that most contributed to the variation between habitats were: Interception between M and wing border, interception dm-cu, and interception between Cu and dm-cu. The wing morphometric variations observed in L. marginata could be associated with phenotypic plasticity.